Ehrlichia chaffeensis and Four Anaplasma Species With Veterinary and Public Health Significance Identified in Tibetan Sheep (Ovis aries) and Yaks (Bos grunniens) in Qinghai, China - Wang, Ye; Zhang, Qingxun; Han, Shuyi; Li, Ying; Wang, Bo; Yuan, Guohui; Zhang, Peiyang; Yang, Ziwen; Zhang, Heng; Sun, Yali; Chen, Jiyong; Han, Xueqing; et al. (Frontiers in Veterinary Science, 2021)
Tick-borne diseases (TBDs) can cause serious economic losses and are very important to animal and public health. To date, research on TBDs has been limited in Qinghai-Tibet Plateau, China. This epidemiological investigation was conducted to evaluate the distribution and risk factors of Anaplasma spp. and Ehrlichia chaffeensis in livestock in Qinghai. A total of 566 blood samples, including 330 yaks (Bos grunniens) and 236 Tibetan sheep (Ovis aries) were screened. Results showed that A. bovis (33.3%, 110/330) and A. phagocytophilum (29.4%, 97/330) were most prevalent in yaks, followed by A. ovis (1.2%, 4/330), A. capra (0.6%, 2/330), and E. chaffeensis (0.6%, 2/330). While A. ovis (80.9%, 191/236) and A. bovis (5.1%, 12/236) infection was identified in Tibetan sheep. To our knowledge, it is the first time that A. capra and E. chaffeensis have been detected in yaks in China. Apart from that, we also found that co-infection of A. bovis and A. phagocytophilum is common in yaks (28.2%, 93/330). For triple co-infection, two yaks were infected with A. bovis, A. phagocytophilum, and A. capra, and two yaks were infected with A. bovis, A. phagocytophilum, and E. chaffeensis. Risk analysis shows that infection with A. bovis, A. phagocytophilum, and A. ovis was related to region and altitude. This study provides new data on the prevalence of Anaplasma spp. and E. chaffeensis in Qinghai, China, which may help to develop new strategies for active responding to these pathogens.